(3GdWH GdfHhjs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjfhHYO agPG cJGH LeYJ ajg GdCMGOjK GdhGQOI aj GdWH eQJHI Ydi GdCHhGH hCHjf MGd GdMOjK UMI hMSfG hVYaGs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3CfG YHO Gddg Hf eMeO GdUhi KfG eMeO Hf LYaQ GdhQcdj CfG SYjO Jbj Hf ejSQI Yf CfSs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B886(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3cTa GdXfhf(B: 2 / 1095s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs